Defining the Decision-to-Delivery Interval at Cesarean Section: Narrative Literature Review and Proposal for Standardization. Issue 4 (21st December 2022) - May, R.L.; Clayton, M.A.; Richardson, A.L.; Kinsella, S.M.; Khalil, A.; Lucas, D.N.
Abstract : ( Anaesthesia . 2022;77:96–104. doi: 10.1111/anae.15570) The 30-minute decision-delivery interval for emergency cesarean delivery (CD) is a deeply embedded and widely studied standard for the evaluation of outcomes in high-resource settings. Despite the self-evident nature of the term, there is no consensus for what specifically defines the instance of "decision, " "delivery, " "incision, " or other timepoints related to carrying out the surgery. This review investigates how these terms have been used in publications in the preceding 40 years, and how inconsistent approaches may undermine the utility of this framework.